1999
DOI: 10.1001/archopht.117.9.1223
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Based Learning in Ophthalmology

Abstract: To gain experience with problem-based learning as a demonstration project in a medical school's curriculum renewal effort and determine if using a single facilitator to circulate among the small groups would yield positive results. Design: We developed 16 cases around 4 ophthalmic problems that were used in 3-hour small-group sessions during the Introduction to Clinical Medicine semester of the second-year curriculum. A single faculty member facilitated the small groups of 4 students each that were created by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…As students noted their increased interest as a result of having PBL cases, they spent more time working on ophthalmology, and their test scores were greatly improved. 23 A great challenge for ophthalmology in medical school education 24 is that PBL was rarely applied in the ophthalmology curriculum in Chinese medical colleges until recently. Reasons include: (1) ophthalmology is usually a subsidiary course, (2) the schedule is tight, (3) there is perceived to be too much content to convey, and (4) ophthalmology is more complicated and less easy for students of general medicine to grasp compared with other medical specialty areas.…”
Section: Strongly Disagreementioning
confidence: 99%
“…As students noted their increased interest as a result of having PBL cases, they spent more time working on ophthalmology, and their test scores were greatly improved. 23 A great challenge for ophthalmology in medical school education 24 is that PBL was rarely applied in the ophthalmology curriculum in Chinese medical colleges until recently. Reasons include: (1) ophthalmology is usually a subsidiary course, (2) the schedule is tight, (3) there is perceived to be too much content to convey, and (4) ophthalmology is more complicated and less easy for students of general medicine to grasp compared with other medical specialty areas.…”
Section: Strongly Disagreementioning
confidence: 99%
“…These studies were varied in their methodology, were performed in different geographic zones, and normally analysed the experience of just one education centre. Most studies (53) reported superiority of PBL in learning and knowledge acquisition (Sokas et al 1990;Richards et al 1996;Gresham & Philp 1996;Hill et al 1998;Blake & Parkison 1998;Hmelo 1998;Finch 1999;Casassus et al 1999;Purdy et al 1999;Farrell et al 1999;Finch 1999;Curtis et al 2001;Trevena & Clarke 2002;Astin et al 2002;Whit eld et al 2002;Whit eld et al 2002;McParland et al 2004;Casey et al 2005;Gurpinar et al 2005;Tamblyn et al 2005;Abu-Hijleh et al 2005;Distlehorst et al 2005;Distlehorst et al 2005;Hoffman et al 2006;Kong et al 2009;Tsou et al 2009;Tsou et al 2009;Wang et al 2010;Abou-Elhamd et al 2011;Urrutia et al 2101;Tian et al 2012;Hoover et al 2012;Li et al 2013;Ding et al 2014;Meo 2014;Khoshnevisasl et al 2014;Al-Drees et al 2015;Al-Shaikh et al 2015;Hande et al 2015;González et al 2015;Yanamadala et al 2016;Balendran & John 2017;…”
Section: Learning and Knowledge Retentionmentioning
confidence: 99%
“…The few studies conducted in the context of PBL in ophthalmology have also suggested that PBL has a definite positive influence in the ophthalmology teaching-learning process. [910111213]…”
Section: Problem-based Learning In Ophthalmologymentioning
confidence: 99%
“…A study by Kong et al,[9] compared three types of learning process—normal didactic teaching, PBL based on digital cases and conventional PBL. The total sample size was 90 students and they were divided into three groups of 30 each.…”
Section: Problem-based Learning In Ophthalmologymentioning
confidence: 99%
See 1 more Smart Citation